Rhamphomyia Meigen of the Canadian Arctic Archipelago, Greenland and Iceland (Diptera: Empididae) - Sinclair, Bradley J.; Vajda, Élodie A.; Saigusa, Toyohei; Shamshev, Igor V.; Wheeler, Terry A. (Zootaxa, 2019)
Rhamphomyia of the Canadian Arctic Archipelago, Greenland and Iceland, comprising 23 species, including five new species, are revised: R. (Ctenempis) albopilosa Coquillett, R. (Dasyrhamphomyia) erinacioides Malloch, R. (Dasyrhamphomyia) hovgaardii Holmgren, R. (Dasyrhamphomyia) leptidiformis Frey, R. (Dasyrhamphomyia) nigrita Zetterstedt, R. (Eorhamphomyia) shewelli Sinclair, Vajda, Saigusa & Shamshev sp. nov., R. (Pararhamphomyia) diversipennis Becker, R. (Pararhamphomyia) filicauda Henriksen & Lundbeck, R. (Pararhamphomyia) frigida Sinclair, Vajda, Saigusa & Shamshev sp. nov., R. (Pararhamphomyia) helleni Frey, R. (Pararhamphomyia) hilariformis Frey, R. (Pararhamphomyia) hoeli Frey, R. (Pararhamphomyia) kjellmanii Holmgren, R. (Pararhamphomyia) lymaniana Sinclair, Vajda, Saigusa & Shamshev sp. nov., R. (Pararhamphomyia) omissinervis Becker, R. (Pararhamphomyia) petervajdai Sinclair, Vajda, Saigusa & Shamshev sp. nov., R. (Pararhamphomyia) septentrionalis Sinclair, Vajda, Saigusa & Shamshev sp. nov., R. (Pararhamphomyia) simplex Zetterstedt, R. (Pararhamphomyia) ursinella Melander, R. herschelli Malloch, R. hirtula Zetterstedt, R. laevigata Loew, R. setosa Coquillett. The following six new synonyms are proposed: R. calvimontis Cockerell, 1916 and R. wuorentausi Frey, 1922 = R. albopilosa Coquillett, 1900; R. fridolini Frey, 1950 = R. laevigata Loew, 1861; R. hirticula Collin, 1937 = R. setosa Coquillett, 1895; R. uralensis Becker, 1915 = R. kjellmanii Holmgren, 1880; R. zaitzevi Becker, 1915 = R. hovgaardii Holmgren, 1880. Lectotypes are designated for the following species: R. diversipennis Becker, R. filicauda Henriksen & Lundbeck, R. helleni Frey, R. herschelli Malloch, R. hirticula Collin, R. hoeli Frey, R. leptidiformis Frey, R. omissinervis Becker, R. setosa Coquillett, R. uralensis Becker, R. wuorentausi Frey, R. zaitzevi Becker. A neotype is designated for R. laevigata Loew. Keys to male and female species of Rhamphomyia and distribution maps of this region are provided. DNA barcode data are presented for 16 species of arctic Rhamphomyia.